Strategies for Resection Using Portal Vein Embolization: Metastatic Liver Cancer - Elias, Dominique; Goere, Diane; Kohneh-Sahrhi, Niaz; de Baere, Thierry; Madoff, David C; de Baere, Thierry (Seminars in Interventional Radiology, 2008)
The oncological landscape is constantly changing with the development of new curatively intended therapeutic strategies. More and more, liver metastases are amenable to resection following the progress achieved as a result of new oncological concepts (i.e., treat detectable disease with surgery and ablative therapies and treat the remaining nondetectable disease with efficient chemotherapy) as well as improved chemotherapeutic and ablation techniques. One of the major limitations to extending the indications for liver resection is the volume of the future remnant liver (FRL). To overcome these limitations, portal vein embolization (PVE) has played a key role in obtaining preoperative hypertrophy of the FRL and thus has reduced postoperative morbidity and mortality. Interestingly, thermal ablation of multiple bilateral liver metastases makes it difficult to predict the volume of parenchyma scheduled for ablation. Furthermore, prolonged chemotherapy impairs liver parenchyma function, which has a negative impact on liver hypertrophy. In the future, both volumetric and functional assessment of the FRL will be used to determine whether PVE is necessary before hepatectomy in individual patients and new strategies (e.g., PVE used alone or combined with other treatments; timing of PVE may vary) will be based on these principles. This article presents various current strategies for the use of PVE in patients with metastatic liver cancer.
Keywords: Portal vein embolization; liver metastases; combined treatments